Review of the subgenus Gerris s.str. in China (Hemiptera: Gerridae), with description of a new species from the Tibetan Plateau - Zhang, Beichen; Leng, Zhaoqi; Ye, Zhen (Zootaxa, 2026)
The subgenus Gerris (Gerris s.str.) Fabricius, 1794 in China is reviewed. Gerris xizangensis sp. nov. from Jilong, Xizang is described. Additionally, two species, G. argentatus Schummel, 1832, and G. curvus Tran & Polhemus, 2012, are reported for the first time from China. Diagnoses and new distribution records are provided for eight species previously recorded from China: G. angulatus Lundblad, 1934, G. babai Miyamoto, 1958, G. lacustris (Linnaeus, 1758), G. latiabdominis Miyamoto, 1958, G. lobatus Andersen & Chen, 1993, G. nepalensis Distant, 1910, G. odontogaster (Zetterstedt, 1828), and G. sahlbergi Distant, 1879. Photographs of diagnostic characteristics of both sexes, in-situ habitus, and distributional maps are presented, along with an identification key of the subgenus Gerris s.str. occurring in China.